U.S. Territorial Exclusion in Federal Sentencing Research: Can it be Justified? - Bumphus, Vic (2014)
There is a dearth of knowledge on sentencing process and outcomes in Guam, the Northern Mariana Islands, Puerto Rico and the United States Virgin Islands. It is not uncommon for researchers conducting national studies to intentionally exclude data from these American territories. Their actions have been justified on the grounds that territories have "distinctive" characteristics that warrant exclusion. Using federal sentencing data, this study explores whether the sentencing patterns observed in the territories are as "unique" as scholars assume and if so, in what ways and to what extent. Descriptive analysis reveals that attributes of offenders and case processing strategies are similar across the U.S. mainland and its territories. Although multivariate analysis revealed some notable differences (e.g., territories are more punitive than states) the larger finding is that there are more similarities than differences with regards to the processing of cases and outcomes. Implications of the study and directions for future research are discussed